The International Journal of Screendance 2010 - Rosenberg, Douglas (The International Journal of Screendance, 2018)
No abstract available Originally published by Parallel Press, an imprint of the University of Wisconsin-Madison Libraries, as The International Journal of Screendance, Volume 1 (2010), Parallel Press. It is made available here with the kind permission of Parallel Press.